Subtitling Strategies Used in Translating Cultural Words in The Subtitle of Disney Animation Movie: Coco - Monika Rosalia Subrata; Jumanto Jumanto (Journal of linguistics, culture and communication, 2023)
The study aims to identify the subtitling strategies used in translating cultural words in the subtitle of Disney Animation Movie: Coco. This descriptive qualitative study employed the data in words, sentences, and logical arguments related to the topic. The data were English combined with Spanish subtitle as the source language and Indonesian subtitles as the target language. The theories used in the analyzing process and describing the analysis were the classification of cultural words by Newmark (1988:94-103) and the subtitling strategies based on Gottlieb's theory (1992:66). There were 100 cultural words found in the subtitles, which were divided into five classifications of cultural words, namely: Ecology (26%), Material Culture (22%), Social Culture (20%), Gesture and Habit (18%) and also Organization (14%). On the other hand, after the researcher grouped the cultural words, then the words were analyzed using the subtitling strategies theory of Gottlieb (1992), in which the subtitling strategies were divided into ten types: Transfer (41%), Imitation (14%), Transcription (14%), Paraphrase (7%), Expansion (7%), Deletion (4%), Condensation (3%), Dislocation (3%), Decimation (2%), and Resignation (2%). The dominant subtitling strategy in translating the cultural words is Transfer with 41 data. Based on the analysis result, within this mainly used Transfer strategy, the translator directly translated the text, word-to-word, so that the translation result in the subtitle becomes complete and accurate with its literal meaning according to the source language.